Efektivitas Investasi Publik di Era Otonomi Daerah: Studi Kasus Pembangunan PASTY - Herwanto, Trisno Sakti (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
This paper aims to examine the effectiveness of public investment on the public investment of Yogyakarta Animal and Plant Market (PASTY) development. Cost and Benefit Analysis was applied to measure the PASTY values. We found that the investment of PASTY development gives effective impact on welfare with a positive NPV value IDR 26 billion. Factors that affect the effectiveness of the development of PASTY are sound policy formulation process, collaborative action in the policy implementation process, clear fragmentation of work and responsibility of government agencies, and availability of resources.